Nekateri ukrepi za omejevanje širjenja visokega pajesena (Ailanthus altissima (Mill.) Swingle) in smernice za gozdnogojitveno ukrepanje ob vdoru potencialno invazivnih tujerodnih drevesnih vrst v ohranjene gozdove v Sloveniji - Roženbergar, Dušan (Gozdarski vestnik, 2017)
The tree of heaven is one of the most widespread non-native tree species in Slovenia. In most areas, its spread occurs in non-forested areas, yet recent observations indicate it is becoming more common within some forest ecosystems as well. Because chemical treatment is banned in Slovenia, this study tested the effectiveness of three mechanical control treatments. Breakage of annual and biennial shoots was not successful; the best treatment was total removal by pulling seedlings and saplings. Mechanical control of invasive tree species is more effective if combined with other management approaches, such as practicing silviculture that promotes vertically diverse stands of native tree and shrub species, particularly small-scale silviculture that maintains a subcanopy layer.
Keywords: Ailanthus altissima (Mill.) Swingle; tehnike odstranjevanja; tree of heaven; visoki pajesen; control techniques; gojenje gozdov; silviculture; invasive non-native tree species; invazivne tujerodne drevesne vrste; smernice; forest management; gospodarjenje z gozdovi; guidelines